KOMPOSISI NUKLEOTIDA GEN MITOKONDRIA D-LOOP IKAN GLODOK (Periophthalmus argentilineatus Valenciennes, 1837) DARI PANTAI BAROS BANTUL, D.I. YOGYAKARTA - Arisuryanti, Tuty (Fakultas Biologi Universitas Gadjah Mada, 2024)
Indonesia is a country with a larger area of water than land. Consequently, the diversity of organisms inhabiting Indonesian waters is highly varied. Mangroves are one of the aquatic ecosystems found in Indonesia. One type of fish that can be found in the mangrove ecosystem is the barred mudskipper (Periophthalmus argentilineatus). One of the mangrove forests that Periophthalmus argentilineatus can be found is the Mangrove Forest in Baros Beach, Bantul, Special Region of Yogyakarta. The mangrove ecosystem is influenced by tidal cycles, so the barred mudskipper has unique adaptations, such as breathing with gills during high tide and breathing through the skin and the mucus lining of the mouth and throat during low tide or dry conditions, as well as storing water in its gill cavities. However, research on the composition of mitochondrial D-loop nucleotide of the barred mudskipper is still very limited. The data is crucial and can be used in conservation efforts. Therefore, this study aimed to determine the nucleotide composition of the mitochondrial D-loop gene sequence of the mudskipper (Periophthalmus argentilineatus) collected from Baros Beach, Bantul, Special Region of Yogyakarta. DNA extraction was performed on seven mudskipper samples, followed by DNA amplification using universal primers L15995 and H16498 targeting the mitochondrial D-loop gene. The study results showed variations in the nucleotide composition of T, A, C, and G in the seven mudskipper samples, which were 25.77%, 27.35%, 21.46%, and 25.42%, respectively. The average nucleotide composition of A+T was 47.2%, while G+C was 52.77%.